Description of mutation spectrum and polymorphism of Wilms' tumor 1 (WT1) gene in hypospadias patients in the Indonesian population. Issue 3 (June 2018) - Diposarosa, Rizki; Pamungkas, Kurniawan O.; Sribudiani, Yunia; Herman, Herry; Suciati, Lita P.; Rahayu, Nurul S.; Effendy, Sjarif H.
Summary: Introduction: Hypospadias is one of the most common congenital anomalies of the penis. Previous studies reported mutation of the Wilms' tumor 1 (WT1) gene as a cause of hypospadias. The aim of this study is to describe the WT1 mutation spectrum and polymorphism in hypospadias patients in Indonesia. Material and methods: DNA was isolated from 74 hypospadias patients at the Division of Pediatric Surgery, Department of Surgery Hasan Sadikin Hospital. All exons in the WT1 gene were amplified by a PCR method, followed by Sanger sequencing. Mutation analysis was performed using BioEdit software and in silico analysis using Mutation Taster, Polymorphism Phenotyping-2 (PolyPhen-2), and Sorting Intolerant from Tolerant (SIFT). Result: DNA analysis results showed two types of heterozygous mutations in five subjects (Table), hence the frequency of WT1 mutations was 6.7% (10/148 allele). The first mutation was a missense mutation identified in twin boys. The second was a novel heterozygous alteration in the non-coding region nine bp upstream of exon 6 (c.366-9T>C), which was identified in three patients. One heterozygous polymorphism in the coding region of exon 7 (c.471A>G/rs16754) was identified in 10 subjects. This variant did not cause any change in amino acid products (silence polymorphism). Allele frequency for the G allele (mutant allele) and A allele (wild type) was 13.5% and 86.5%, respectively. Discussion: WT1 is one of the best known hypospadias genes. The WT1 gene is involved in male genital development in the early and late periods of sex determination, and hence is known as a long-term expression gene in genitalia development. Mutation analysis of WT1 in a Chinese population identified that the WT1 mutation frequency was 4.4%. The WT1 mutation frequency identified in the present study was higher, at 6.7%. Coincidentally, research subjects with p.R158H variants were monozygotic twin siblings with midshaft hypospadias accompanied by undescended testis in one and penoscrotal hypospadia with micropenis in the other. The incidence of familial hypospadias in male siblings suffering from hypospadias was reported to be 9.6% in a study conducted by Sorensen et al. Moreover, in the present study polymorphism c.471A>G(rs16754) at exon 7 was identified heterozygously in 10 research subjects (minor allele frequency 13.5%). Conclusion: WT1 mutations were identified in only a few cases of hypospadias and most of these were syndromic. This result implies that mutation of WT1 is not a common cause of hypospadias in the Indonesian population. Table Rare variant gene WT1 Sample number Exon DNA alteration Amino acid alteration Allele SNP Phenotype Type of hypospadias Associated anomalies 5 Int6 c.366-9T>C – Het – Mid-shaft – 6 Int6 c.366-9T>C – Het – Mid-shaft – 41 Int6 c.366-9T>C – Het – Penoscrotal Undescended testis Anorectal malformation 56 7 c.473G>A p.R158H Het rs554416372 Mid-shaft Undescended testis 57 7 c.473G>A p.R158H Het rs554416372 Penoscrotal Micropenis